PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU YANG DIMODERATING OLEH SUPERVISI (STUDI KASUS PADA SMA NEGERI DI KECAMATAN TAPUNG) - Ramefa, Yuli; Indarti, Sri; Efni, Yulia (Jurnal Tepak Manajemen Bisnis, 2018)
The specific goal of this research was to test on how supervisionmoderates the effect of competency and motivation toward senior high schoolteacherâs work performance in TapungDistrict. The use of this research was toexplain and to enlarge the previous research about the effect of work motivationand professional competency toward teacherâs work performance. The populationof this research was 106 teachers of Public Senior High School in TapungDistrict. This research used primer data with scale likert of five variables. Thisresearch used regression Analyze model approach. Method analyzes used wasvalidated test, reliability and linear regression with moderation test. The result ofthe research was shown that competency has a positive and significant effecttoward teacher performance, motivation has positive and significant effect towardteacherâs work performance. Supervision has a positive and significant effecttoward teacherâs work performance. The moderated competency by supervisionwas affected toward teacherâs work performance of Public Senior High School atTapung. A motivation which was moderated by supervision was not effected to thework performance of Public Senior High School teacher at Tapung District.